Release of Radioactive Particulates into the Air during Forest Fire in Riau Province, Indonesia - S Syarbaini; M Makhsun; W Wahyudi; S Syahrial; J Jasmiyati (PPIKSN-BATAN, 2019)
Forest fires are annual problem during the dry season and become a biggest threat to forest resources in Indonesia. The forest fires release into the atmosphere large quantities of particulate matter and volatilized substances. The present study investigates effects of forest fire on air quality in the case of a radiological event of ashes from forest fires emissionsin Riau province during an intense forest fire season that occurred in 2015.Atmospheric aerosol samples were collected from Mayto December, 2015 using a large volume TSP (total suspended particles) sampler.Concentrations of radionuclidesin airborne particulate matter were measured by using gamma spectrometry.It was shown that the activity concentrations of 226Ra, 232Th and 40K ranged from 0.026 to 0.114 mBq/m3, 0.005 to 0.011 mBq/m3 and 0.99 to 5.64 mBq/m3, respectively. The activity concentrations of 137Cs in air was found lower than the minimum detectable activity of the gamma counting systems (<MDA), except for July and September 2015. The result showed that the smokefrom forest fires contain radioactive particulates, which may have a potential health risk of population, and need to be considered in forest fire disaster. Inhaled smoke particles from forest fires may contribute to enhanced radiation doses to the general public.